Respuesta :
Answer:
b = -1
Step-by-step explanation:
7(3b-1): 7 goes into the numbers by multiplying. This will give you 21b-7.
So now the equation should be like 21b-7=2b-26.
-7 and 2b swap places, making 21b-2b=7-26. It will give you 19b= -19.
Finally divide the two numbers (-19 / 19) and the solution will be b= -1.
If I didn't make a clear answer or a good explanation, please comment. I sometimes mess up my steps, and this is my first time using this.
Answer:
b = -1
Step-by-step explanation:
7(3b -1 ) = 2b - 26
First, distribute.
21b - 7 = 2b - 26
Then, add 7 to both sides AND subtract 2b on both sides
21b - 7 + 7 - 2b = 2b - 2b - 26 + 7
Add common terms
19b = -19
Divide by 19
b = -1